The implementation of the Kinyoun staining technique in a resource-limited setting is feasible and reveals a high prevalence of intestinal cryptosporidiosis in patients with HIV. (September 2022) - Mesfun, Million Getachew; Fuchs, Andre; Holtfreter, Martha Charlotte; Tufa, Tafese Beyene; Orth, Hans Martin; Luedde, Tom; Feldt, Torsten
Abstract: Objectives: In resource-limited settings, intestinal Cryptosporidial or coccidian infections are common causes of chronic diarrhea but usually remain undiagnosed by routine stool investigation. Here, the addition of the Kinyoun staining technique after stool concentration was evaluated as an easy and inexpensive method for diagnosis of intestinal parasitic infection in patients with HIV. Methods: This cross-sectional study investigated patients with HIV with diarrhea and randomly selected patients with HIV without diarrhea as controls. Stool samples were examined by wet mount microscopy and Kinyoun staining after stool concentration. Clinical, sociodemographic, and behavioral data were collected. Statistical analysis was performed using chi-squared test and multivariate regression analysis. Results: In total, 163 participants were included (62.0% female, mean age 38.2 [SD ± 10.7] years). Diarrhea was present in 52.1% (85/163). The prevalence of intestinal parasites was 18.4% (30/163). Cryptosporidial infections were more frequent among patients with diarrhea (12.9% [11/85] vs 1.3% [1/78], P = 0.005) and in patients with CD4 + cell count <200 cells/µl (25.9% [7/27] vs 3.7% [5/136], P = 0.001). Risk factors for intestinal parasitic infections were diarrhea and the habit of regularly eating uncooked food. Kinyoun staining was necessary for the detection of cryptosporidiosis. Conclusion: In our cohort, the prevalence of intestinal parasitic infection was high, especially after additional use of Kinyoun staining for detection of Cryptosporidia or intestinal coccidia. Considering its clinical relevance, particularly in individuals at risk, the implementation of this technique should be considered in resource-limited settings.